2013
DOI: 10.1007/s00737-013-0371-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated risk of adverse obstetric outcomes in pregnant women with depression

Abstract: Objective In this study, we evaluated the association between patient depression ratings at an initial obstetrics visit and adverse birth outcomes in African-American women. Study Design We conducted a retrospective cohort study of 261 pregnant, African American women who were screened with the Edinburgh Postnatal Depression Scale (EPDS) at their initial prenatal visit. Medical records were reviewed to assess pregnancy and neonatal outcomes, specifically pre-eclampsia, preterm birth, intrauterine growth reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 38 publications
1
66
0
3
Order By: Relevance
“…The presence of symptoms suggesting a diagnosis of probable depressive disorder was verified in 14.4% of the pregnant women evaluated; although this finding is lower than that of other countries, ranging from 22.0% to 34.9%, 17,19 our results are similar to the national studies performed with low socioeconomic pregnant women in the second and third trimesters of pregnancy 6,24 . The association between depression and obstetric outcomes is still poorly understood.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The presence of symptoms suggesting a diagnosis of probable depressive disorder was verified in 14.4% of the pregnant women evaluated; although this finding is lower than that of other countries, ranging from 22.0% to 34.9%, 17,19 our results are similar to the national studies performed with low socioeconomic pregnant women in the second and third trimesters of pregnancy 6,24 . The association between depression and obstetric outcomes is still poorly understood.…”
Section: Discussionsupporting
confidence: 76%
“…The association between depression and obstetric outcomes is still poorly understood. However, some studies have pointed to this disorder as a possible risk factor for low birth weight and prematurity 6,17,25 . In this study, no association was found between probable diagnosis of depressive disorder and LBW and prematurity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that maternal depression during pregnancy may be in an important risk factor for LBW and SGA; thus, maternal depressive symptomatology was included as a covariate. 33,34 Data analysis Preliminary analyses examined sociodemographic variables and key study variables to assess distribution of data, and to identify potential outliers and collinearity among variables. T-tests and chi-square analyses were used for continuous and categorical variables respectively.…”
Section: Possible Correlates Of Adverse Neonatal Outcomesmentioning
confidence: 99%
“…The impact to the mother can be devastating as up to 3% of all pregnant women and 30% of depressed pregnant women report suicidal ideation. 4,5 The infant is also at risk as in untreated women, antenatal depressive symptoms have been linked to serious adverse birth outcomes 6 such as preterm birth, 7,8 lower birth weight, 9,10 pre-eclampsia, 11 and abnormal infant neuroendocrine development, 12 which all have significant long-term health and economic impacts. Beyond the immediate postpartum period, AD continues to have a negative health impact, as it has been associated with impairment in maternalfetal attachment and abnormal child development.…”
mentioning
confidence: 99%